Application of Fat Grafting in Cosmetic Breast Surgery - Davis, Matthew J. (Semin Plast Surg, 2020)
The role of fat grafting to the breasts has evolved in the recent past, gaining several new applications within both reconstructive and aesthetic surgery. Initially used for reconstructive purposes to fill lumpectomy defects or to correct residual contour deformities after breast reconstruction, it has since made its way into cosmetic breast surgery and has grown to encompass a wide variety of new indications. Fat grafting in aesthetic breast surgery may be performed as a form of primary autologous breast augmentation or as an adjunct to implant-based breast augmentation to disguise implant edges. It may also be used to provide added volume after explant surgery or to provide improvements in breast contour alongside mastopexy techniques. In this article, we will review the current applications of fat grafting in aesthetic breast surgery and provide an up-to-date summary of its reported outcomes, safety, and complications.